2002
DOI: 10.1034/j.1600-0412.2002.810102.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin receptor in human endometriotic tissues

Abstract: The PRLR is expressed in normal endometrium, while cells of the endometriotic tissues did not express the PRLR, at least during the mid-late proliferative phase of the menstrual cycle. The absence of the PRLR in the endometriotic tissues could not be correlated with the serum prolactin levels. These results suggest the existence of differential regulation of PRLR expression between normal and endometriotic tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…We found very strong LD across the PR locus. Serum prolactin levels have been implicated as a cause for infertility in patients with minimal to mild endometriosis (Gregoriou et al, 1999;Martinez et al, 2002). The promoter SNP rs10895068 was associated with prolactin levels in a population sample (Westberg et al, 2004); although this SNP did not show individual association with endometriosis in our families, or in the subset with minimal-mild endometriosis and subfertility, it may warrant further investigation.…”
Section: Discussionmentioning
confidence: 65%
“…We found very strong LD across the PR locus. Serum prolactin levels have been implicated as a cause for infertility in patients with minimal to mild endometriosis (Gregoriou et al, 1999;Martinez et al, 2002). The promoter SNP rs10895068 was associated with prolactin levels in a population sample (Westberg et al, 2004); although this SNP did not show individual association with endometriosis in our families, or in the subset with minimal-mild endometriosis and subfertility, it may warrant further investigation.…”
Section: Discussionmentioning
confidence: 65%
“…Although some antibodies targeting PRLR have been shown to reduce tumor malignancy by blocking autocrine/endocrine PRL activ-ities (6,7), the full-length PRLR gene product was not detected in endometriosis tissues (8). Our results from screening an array of human uterine cancer cells indicated that transcriptionally spliced isoforms of PRLR products might be responsible for mediating activities of the tumoral PRL/PRLR axis.…”
Section: Introductionmentioning
confidence: 66%
“…Both PRL-R and GH hormones are known to contribute to this process through their autocrine/paracrine actions. Additionally, IGF1 and IGF2, which are downstream targets, are involved in regulating cellular growth and differentiation (69). The significance of prolactin family members in uterine development and endometrial adenogenesis has been well established (70).…”
Section: Role Of Adenogenesis In Endometriosismentioning
confidence: 99%